Pharyngeal electrical stimulation for treatment of dysphagia in subacute stroke - Bath, Philip M.W.; Scutt, Polly; Love, Jo; Clavé, Pere; Cohen, David; Dziewas, Rainer; Iversen, Helle K.; Ledl, Christian; Ragab, Suzanne; Soda, Hassan; Warusevitane, Anushka; Woisard, Virginie; et al. (American Heart Association, 2016)
Background and Purpose: Dysphagia is common after stroke, associated with increased death and dependency, and treatment options are limited. Pharyngeal electric stimulation (PES) is a novel treatment for poststroke dysphagia that has shown promise in 3 pilot randomized controlled trials. Methods: We randomly assigned 162 patients with a recent ischemic or hemorrhagic stroke and dysphagia, defined as a penetration aspiration score (PAS) of ≥3 on video fluoroscopy, to PES or sham treatment given on 3 consecutive days. The primary outcome was swallowing safety, assessed using the PAS, at 2 weeks. Secondary outcomes included dysphagia severity, function, quality of life, and serious adverse events at 6 and 12 weeks. Results: In randomized patients, the mean age was 74 years, male 58%, ischemic stroke 89%, and PAS 4.8. The mean treatment current was 14.8 (7.9) mA and duration 9.9 (1.2) minutes per session. On the basis of previous data, 45 patients (58.4%) randomized to PES seemed to receive suboptimal stimulation. The PAS at 2 weeks, adjusted for baseline, did not differ between the randomized groups: PES 3.7 (2.0) versus sham 3.6 (1.9), P=0.60. Similarly, the secondary outcomes did not differ, including clinical swallowing and functional outcome. No serious adverse device-related events occurred. Conclusions: In patients with subacute stroke and dysphagia, PES was safe but did not improve dysphagia. Undertreatment of patients receiving PES may have contributed to the neutral result. Clinical Trial Registration: URL: http://www.controlled-trials.com. Unique identifier: ISRCTN25681641.